EKSPLORASI DAN IDENTIFIKASI JAMUR TRICHODERMA SP DENGAN METODE PENGENCERAN SEBAGAI AGEN HAYATI DI LABORATORIUM AGENS HAYATI UPT PROTEKSI TANAMAN PANGAN DAN HORTIKULTURA JAWA TIMUR - Fatimatul Ula, Siti; Misnati Nur Indahsari, Wiwin (Universitas Cokroaminoto Palopo, 2025)
This study aims to determine the results of Trichoderma sp fungus exploration in healthy bamboo and chili horticulture land and dense chili and to determine the macroscopic and microscopic characteristics of Trichoderma sp fungus as a biological agent. This type of research is descriptive exploratory with tools and materials, namely Aquades, 70% alcohol, PDA media, potatoes, technical agar, dextrose, chloramphenichol, tomato soil samples, healthy chili soil, dense chili soil, bamboo soil, tissue, methylated spirits, LPG, plastic wrap, cotton, label paper. The tools used are hoes, scoops, rulers, PH meters, rapitest, Laminar air flow, Ose needles, Petri dishes, test tubes, Erlenmeyer flasks, L sticks, Vortex, Plastic, Plastic boxes, Bunsen burners, stoves, sterilization pans, autoclaves, tube racks, tweezers, microscopes, glass objects, cover glasses, scales, trays, 1cc syringes, black cloth. Based on the results of exploration and identification activities, Trichoderma sp fungi were obtained with the dilution method precisely at a dilution level of 10-7. In addition, Trichoderma sp fungi were found in tomato soil. The diversity of fungi in tomato plants depends on environmental conditions. The value of tomato rhizosphere diversity in non-endemic is H'> 3.